2022
DOI: 10.21203/rs.3.rs-2020456/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hindcasting injection-induced aseismic slip and microseismicity at the Cooper Basin Enhanced Geothermal Systems Project

Abstract: There is a growing recognition that subsurface fluid injection can produce not only earthquakes, but also aseismic slip on faults. A major challenge in understanding interactions between injection-related aseismic and seismic slip on faults is identifying aseismic slip on the field scale, given that most monitored fields are only equipped with seismic arrays. We present a modeling workflow for evaluating the possibility of aseismic slip, given observational constraints on the spatial-temporal distributionof mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Wang and Dunham (2022) successfully reconstructed the seismicity observed during fluid injection in the Cooper Basin, Australia, using a numerical model that assumes a velocity‐strengthening fault, explained by the potential presence of phyllosilicates in the fault zone. For the Soultz 1993 sequence, the presence of repeating events, asperity interactions, slip rate decay suggest that the observed seismicity is due to a combined effect of velocity‐weakening on seismic asperities embedded in a velocity‐strengthening matrix (Figure 3, Bourouis & Bernard, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wang and Dunham (2022) successfully reconstructed the seismicity observed during fluid injection in the Cooper Basin, Australia, using a numerical model that assumes a velocity‐strengthening fault, explained by the potential presence of phyllosilicates in the fault zone. For the Soultz 1993 sequence, the presence of repeating events, asperity interactions, slip rate decay suggest that the observed seismicity is due to a combined effect of velocity‐weakening on seismic asperities embedded in a velocity‐strengthening matrix (Figure 3, Bourouis & Bernard, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Similar observations have been made in association with anthropogenic injections at depth; for example, a swarm in the Brawley, California geothermal field in 2012 was preceded and likely triggered by an aseismic slip transient (Wei et al., 2015), while hydraulic fracturing injections in northwestern Canada led to two major slow slip episodes not accompanied by significant seismic events (Eyre et al., 2022). Numerical modeling also showed that fluid injection can trigger aseismic transients, which in turn can trigger seismicity (Eyre et al., 2019; Wang & Dunham, 2022; Wynants‐Morel et al., 2020).…”
Section: Introductionmentioning
confidence: 99%